Dietary Patterns and Perceptions in Older Adults With Chronic Kidney Disease in the Canadian Frailty Observation and Interventions Trial (CanFIT): A Mixed-Methods Study. (November 2022) - Sin, Derek; Harasemiw, Oksana; Curtis, Sarah; Iman, Yasmin; Buenafe, Jeann; DaCosta, Julia; Mollard, Rebecca C.; Tangri, Navdeep; Protudjer, Jennifer L. P.; Mackay, Dylan
Background: People living with chronic kidney disease (CKD) have identified diet as an important aspect of their life and care. Understanding current consumption patterns in this population, and how they relate to patient perspectives of dietary recommendations, may help identify and design potential dietary intervention strategies in CKD. Objective: To investigate the dietary intake patterns of people with advanced-stage CKD, as well as subjective perspectives regarding dietary recommendations from participants and their caregivers. Design: Mixed-methods study with a sequential explanatory design. Setting: Manitoba, Canada. Participants: Individuals with late-stage CKD (CKD stages G4-G5, including dialysis) participating in the Canadian Frailty Observation and Interventions Trial (CanFIT). Methods: First, quantitative data were collected via a cross-sectional dietary assessment, using three 24-hour dietary recalls, a 36-question short diet questionnaire (SDQ), and a Nutrition Quality of Life (NQoL) tool (n = 59). Second, qualitative data were collected during 2 focus groups ( n 1 = 12 and n 2 = 7) held with a subsample of individuals who had completed the dietary surveys, along with their caregivers. Focus groups explored topics related to diet and CKD; transcribed data were analyzed thematically. In the interpretation stage, the qualitative findings were combined with the quantitative results to help explain the latter and reach a deeper understanding of the subjective experiences of adults with CKD. Results: Quantitatively, nearly all (48/51; 94%) participants (mean age 70.8 ± 10.8 years) reported energy intakes below recommendations and most (86%) did not achieve recommended fiber intake. In addition, 15/21 (71%) of patients on dialysis had low protein intake. Qualitatively, 2 themes were identified: (1) Lacking/Needing dietary guidance—incomplete "information overload, " and (2) Experiencing difficulty in adapting to restrictions. Within the former theme, participants spoke of getting too much information at once, often at the wrong time. Within the latter theme, participants spoke of a loss of appetite, and cheating on their dietary recommendations. Limitations: Potential recall bias recalling dietary patterns, small sample size limiting generalizability, self-selection bias. Conclusion: Despite the reported lifestyle changes made by individuals with CKD, which negatively impacted their lives, many had suboptimal nutrition, especially in terms of energy and fiber. In addition, those on dialysis were not eating enough protein, which could be due to changing dietary recommendations as CKD progresses. Qualitative findings provided additional insight into how requisite CKD-dietary changes were perceived and how participants coped with these changes. The timing and delivery of the dietary education within CKD care in Manitoba may not be working for people with CKD as they progress through the disease.